Joni : an unforgettable story - Tada, Joni Eareckson (Zondervan Books, 2021)
"The Christian classic detailing the remarkable events surrounding the 1967 diving accident that left Joni Eareckson Tada paralyzed. This special 45th anniversary edition of Joni commemorates the worldwide impact of her life story to people living with disabilities and includes a new epilogue with updated photos and illustrations by Joni"--